Medication Adherence and Clinical Outcomes towards Oral Hypoglycemic Agents among Type II Diabetic Cohort - Mudaliar, Mohanraj Rathinavelu; Tejashwani, Priyanka Pichala; Ghouse, Ishrar Shaik Mohammad; Bogireddy, Sahithi; Bharat, Gavini Siva; Boreddy, Sasikala (Indian Journal of Pharmacy Practice)
Introduction: Clinical outcomes are measurable clinical parameter which predicts the glycemic control of the disease. Poor adherence to oral hypoglycemic agents remains as one of the main reasons for poor metabolic control. Poor self-management of drug therapy may increase the burden of diabetes to the patient. Materials and Methods: The current prospective observational study of six months duration was performed to assess the adherence of oral hypoglycemic agents and clinical outcomes with reference to patient’s glycemic level in diabetic outpatients of both genders, age greater than 18 years; in a secondary referral hospital of south India. Results: Out of 90 diabetics, 47.78% were male and 52.22% were female; and 37.8% of patients were aged between 61 - 70 years; and 63.31% were prescribed with combination of metformin and glibenclamide, when compared to 22.2% of monotherapy with metformin and the same was directly proportional to their mean medication possession ratio. Our study observed 83.3% of patients were non-adherent to therapy based on their medication possession ratio value, the results also showed that there is significant difference between clinical outcomes in patients based on medication compliance. It was observed that for every 10% increase in medication possession ratio there was improved glycemic control and also significant difference of charlson comorbidity index among patients who are adherent and nonadherent. Conclusion: In conclusion, correlating adherence towards medication use could be a tool to improve and maintain healthoutcomes and quality of life in diabetic cohort populations.
Keywords: Adherence; Charlson comorbidity index; Medication possession ratio; Oral hypoglycemic agents; Outcomes.